The Influence of the Synergy of Pentahelix Elements and Compensation on the Welfare of Hotels’s Employees During the Covid – 19 Pandemic in the City of Makassar - Muh. Ersyad Nasir; Atang Sabur; Leo Sutanto (Journal La Bisecoman, 2024)
This study aims to analyze the synergy of the pentahelix elements, compensation and welfare of hotel employees as well as the effect of the synergy of pentahelix elements and compensation on the welfare of hotel employees during the Covid-19 pandemic in the city of Makassar. This study uses a quantitative descriptive method by processing data obtained from the research location. The population in this study were all hotel employees in the city of Makassar as many as 14,248 people and the number of samples selected was 389 people, using a questionnaire as a research instrument which was then processed using SPSS software version 22 and using Likert scale analysis, partial (t test), simultaneous (F test), multiple linear regression, and the coefficient of determination. The results of the study indicate that the synergy of the pentahelix elements, compensation and welfare of hotel employees affected by the Covid-19 pandemic in Makassar City is considered good. The pentahelix element synergy variable (X1) does not significantly affect the welfare of hotel employees (Y). While the compensation variable (X2) has a positive and significant effect on the welfare of hotel employees (Y). However, simultaneously, the synergy of the pentahelix and compensation elements has a positive and significant impact on the welfare of hotel employees during the Covid-19 pandemic in the city of Makassar.